Multifunctional Nanocomposite Films for Synergistic Delivery of bFGF and BMP-2 - Qi, Wei (ACS Omega, 2017)
[Image: see text] The development of novel materials capable of delivering multiple growth factors is urgent and essential for rapid and effective tissue regeneration. In this study, a kind of composite film composed of poly-l-lysine (PLL), heparin (Hep), and Au nanoparitcles (Au nps) has been fabricated to deliver the basic fibroblast growth factor (bFGF) and bone morphogenetic protein-2 (BMP-2) simultaneously. The films have been found to show enhanced mechanical property due to the incorporation of Au nps. They have also shown good anticoagulation activity with long activated partial thromboplastin time because of the contribution of Hep molecules. Moreover, the osteogenesis studies reveal that the loaded bFGF and BMP-2 in the composite films have a synergistic differentiation effect on mesenchymal stem cells, as indicated by alkaline phosphatase (ALP) activity assay and collagen type I (Col-I) gene expression. In contrast to the (PLL/Hep)(6)/BMP-2/(PLL/Au nps)(6)/(PLL/Hep)(6) and (PLL/Hep)(6)/(PLL/Au nps)(6)/(PLL/Hep)(6)/bFGF films, the (PLL/Hep)(6)/BMP-2/(PLL/Au nps)(6)/(PLL/Hep)(6)/bFGF films have shown higher ALP activity and higher Col-I expression level. Therefore, the developed multifunctional films could be potentially used as osteoinductive coatings of biomaterials. Particularly, this simple and convenient strategy provides an effective approach for the immobilization of multiple growth factors, which may be extended to other bioactive systems for the development of novel multifunctional bioactive surfaces.